PELATIHAN PERAWATAN DAN PERBAIKAN KOMPUTER UNTUK SISWA SD NEGERI KUNATENA - Abdullah, Ibrahim; Tang, Holia Yuliana; Letlay, Martinus Yuliana; Yetimau, Hilarius V.; Malaikokal, Imanuel V.; Hingmadi, Gregorus V.; Fantang, Imelda Maria; Busra, Rustojo Maria; Molina, Jon Idrison (Intimas, 2025)
understanding of grade 5 and 6 students of Kunatena State Elementary School regarding the importance of computer maintenance and repair through computer hardware and software training activities. This training activity was carried out at the Kunatena State Elementary School building. This activity lasted for 1 day on Saturday, November 15, 2024 at 13.00-16.00 WIT. The resource person provided material on the various main components of a computer and how to perform maintenance and repair on the computer. In addition, this community service activity also discussed maintenance and repair on various hardware such as laptops, printers, monitors, mice, keyboards, hard disks, RAM, motherboards, power supplies, processors, CD/DVD drives, sound cards, video cards, BIOS, and OS. The results of this training activity are to improve the understanding and abilities of grade 5 and 6 students of Kunatena State Elementary School in maintaining and repairing computers and their hardware, so that they can save time and money and extend the life of the device.